Sosialisasi Budidaya Edamame Menggunakan Arang Hayati di Kelompok Tani Maju Rajati Desa Rasau Jaya Tiga, Kabupaten Kubu Raya - Shinta Rosalina; Agus Suyanto; Setiawan (LPPM Universitas Panca Bhakti, 2026)
Edamame (Glycine max (L.) Merr.) is a vegetable soybean crop with high economic value and significant market potential. Maju Rajati Farmers Group in Rasau Jaya Tiga Village, Kubu Raya Regency faces challenges in optimizing edamame production due to poor soil conditions and limited knowledge of biochar application. This community service activity aimed to improve farmers' knowledge and skills in edamame cultivation using biochar as a soil amendment. Methods employed included interactive lectures, demonstrations of biochar production from locally available biomass, and direct practice of biochar application on edamame plots. The activity was conducted over three months (September–November 2025) involving approximately 30 active members of the farmer group. Results showed that participants gained substantially improved understanding of biochar benefits for soil structure and fertility enhancement, as well as proper edamame cultivation techniques. Positive responses from participants and their expressed willingness to adopt the technology in subsequent planting seasons indicate the effectiveness of this knowledge transfer initiative. This socialization activity is expected to contribute to increased agricultural productivity and improved farmer welfare in the region.